Iatrogenic Fistula: Types, Causes and Post-repair outcome – 70 cases - Begum, Bilkis (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: In Bangladesh since iatrogenic fistula is gradually increasing so aim of this study is to find out the types, causes and post-repair outcome of iatrogenic fistula. Methods: 70 cases in Bangladesh were reviewed between periodof January 2012 to April 2018. Detailed history, clinical examination and investigations were done to find out the causes. Proper evaluation was done for diagnosis of type of fistula and treatment plan. Results: Among 70 cases, 48 were vault fistulae, 10 intracervical, 7 juxta-cervical, 2 mid-vaginal and 2 at neck region, 1 uretero-vaginal and 1 extensive from neck to cervix. Regarding causes, among 70 cases, 47 fistulae developed after hysterectomy of which 38 following TAH, 6 following caesarean hysterectomy and 3 after vaginal hysterectomy. Rest 16 cases were due to caesarean section, 1 case was following coitus and 6 were due to other than gynecological-obstetric causes. 65 patients were repaired vaginally, 1 abdominally and 4 through combined route. Among 70 cases, 68 patients were successfully repaired at 1st attempt without any significant complication. 2 cases failed at 1st attempt and were dropped out. Conclusions: Almost all of these causes are preventable. So emphasis should be given to identify the causes of iatrogenic fistula to prevent the event. At the same time, our aim is to make these patients free of urinary smell by applying appropriate surgical technique.